Heat-conducting gasket and manufacturing method thereof

By filling the foam metal skeleton with low melting point metal to form a thermal conductivity gasket with a through structure, the problem of low thermal conductivity at high temperatures of high power electronic devices is solved, and efficient thermal conductivity and cost reduction at high temperatures are achieved.

CN119893943APending Publication Date: 2025-04-25江淮前沿技术协同创新中心
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510030619.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing thermal conductivity of existing thermal gaskets at high operating temperatures (for example, 65-140°C) generated by high power electronic devices is low and cannot be used normally.

Method used

Foam metal with a hole structure is used as a skeleton, and the holes are filled with low melting point metal to form a structure in which the low melting point metal on the upper and lower surfaces are penetrated with the low melting point metal inside the intermediate layer. The foam metal of the specific melting point of the thermal gasket remains effectively supported at high temperatures, while the low melting point metal produces microflow at high temperatures, filling interface gaps and improving thermal conductivity.

Benefits of technology

At the higher operating temperature of high-power electronic devices (65-140℃), this thermal conductivity gasket can maintain thermal conductivity, solving the problem of low thermal conductivity of existing thermal conductivity at high temperatures, while reducing the amount of metal indium and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119893943A_ABST
    Figure CN119893943A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a heat-conducting gasket and a preparation method thereof, and belongs to the technical field of heat-conducting materials. The heat-conducting gasket comprises a foam metal framework and low-melting-point metal, the low-melting-point metal comprises upper-layer low-melting-point metal which is distributed on the upper surface of the foam metal framework; internal pores of the foam metal framework are filled with the middle layer low-melting-point metal; the lower-layer low-melting-point metal is distributed on the lower surface of the foam metal framework; the upper-layer low-melting-point metal and the lower-layer low-melting-point metal are communicated through the The melting point of the foam metal framework is greater than 160 DEG C; and the melting point of the low-melting-point metal is 80-160 DEG C and is not lower than the working temperature. The foam metal with the specific melting point serves as a rigid framework material at the high working temperature and can support the heat conduction gasket when the low-melting-point metal is in a micro-melting state, the low-melting-point metal with the specific melting point generates micro-flow at the high working temperature, interface gaps are filled, the heat conduction gasket is tightly attached between two interfaces, and the actual heat conduction capacity of the heat conduction gasket is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present disclosure relate to the technical field of thermal conductive materials, and in particular to a thermal conductive gasket and a manufacturing method thereof. Background Art

[0002] For electronic devices, especially highly integrated semiconductor devices, the development trend is to continuously improve the performance of semiconductor devices and reduce the size of components. Generally speaking, this can be achieved by increasing the number of transistors or clock frequency, and applying more advanced high-density packaging technologies such as hybrid integrated circuits, multi-chip modules (MCMs), and through-silicon vias (TSVs). According to Moore's Law, the number of components that can be accommodated on an integrated circuit will double every 18 months. However, accommodating more components in a smaller package structure means a higher heat flux density; in addition, based on performance optimization considerations, high-power logic units are often concentrated in a certain area of ​​the integrated circuit during chip design, which will cause serious temperature rise in certain areas of the integrated circuit during operation. For every 10°C increase in temperature, the leakage current of the electronic device will increase by about 1 times; therefore, when the operating temperature of the electronic device rises, its overall power consumption will increase sharply, triggering a more severe heating problem, and severe heating will cause a series of usage problems such as reduced reliability of the electronic device. Therefore, the thermal barrier problem has become a bottleneck restricting the sustainable development of electronic devices, and the realization of good thermal management of electronic devices has also received more and more attention and attention from relevant researchers.

[0003] In fact, for thermal management of electronic devices, the transfer of heat from electronic devices to heat sinks is the bottleneck of the entire heat conduction process. Due to the existence of surface roughness, it is often difficult for the surface of electronic devices and heat sinks to achieve ideal surface contact, but point contact in the form of synaptic points, which is bound to cause serious interface gaps; the interface gaps are filled with air, and the thermal conductivity of air is only 0.024W / (m·k), which will seriously hinder the transfer of heat. Therefore, even if the thermal conductivity of the thermal interface material is high, it is still difficult to achieve good heat transfer when the interface gap is large. In addition, the different thermal expansion coefficients of electronic devices and heat sinks should also be taken seriously. Even if the electronic device and the heat sink are well fitted during installation and the interface gap is minimized as much as possible, when the electronic device is in working state, it will inevitably bring about a rise in temperature, and the rise in temperature will cause the material itself to have a volume thermal response; the different thermal expansion coefficients of the electronic device and the thermal interface material will bring different volume thermal response values, which will inevitably cause uneven deformation of the thermal interface, resulting in new interface gaps and affecting the good progress of heat transfer.

[0004] Researchers have tried different materials and methods to improve the bonding and heat transfer process between thermal interface materials and the surfaces of electronic devices. Chinese patent CN105400497A discloses a metal thermal conductive paste, which is a full metal compound including indium, bismuth, tin, and gallium, and is made into a thermal conductive paste that is semi-solid at room temperature, has a melting point of 45°C, and has good viscosity and fluidity, reducing the gaps between the surfaces of thermal interface materials. However, this metal thermal conductive paste has a risk of leakage. Chinese patent CN 118870740 A relates to a thermal conductive material, a preparation method and an application thereof, wherein the thermal conductive material includes a skeleton metal layer and a liquid metal layer, the liquid metal layer is attached to at least part of the surface of the skeleton metal layer, and the liquid metal layer includes a liquid metal matrix and magnetic particles distributed in the liquid metal matrix. The melting point of the liquid metal does not exceed 75°C; the melting point of the material of the skeleton metal layer is not less than 100°C. This structure can exert its excellent thermal conductivity under the working temperature of 50℃ and below, but it cannot be used normally under the working temperature (for example, 65-140℃) generated by high-power electronic devices, and its thermal conductivity is low. Chinese patent CN119031661A relates to a multi-layer composite thermal conductive sheet, including a metal foil, two transition layers arranged on the surfaces of the metal foil on opposite sides, and two low-temperature alloy layers respectively arranged on the surface of a transition layer away from the metal foil; wherein the material of the metal foil is at least one of silver, copper, zinc, and platinum, the material of the transition layer is one of indium or tin, and the melting point of the low-temperature alloy layer is 30-300℃. The hierarchical structure of the thermal conductive sheet is relatively complex, and there is a problem that it cannot be used normally under the high temperature (for example, 65-140℃) generated by high-power electronic devices, and its thermal conductivity is low. Summary of the invention

[0005] In order to solve the above technical problems, the embodiments described herein provide a thermally conductive gasket and a method for manufacturing the same.

[0006] Technical solution of the present invention

[0007] According to a first aspect of the present disclosure, a thermally conductive pad is provided, comprising a foam metal skeleton and a low melting point metal;

[0008] The low melting point metal includes:

[0009] An upper layer of low melting point metal is distributed on the upper surface of the foam metal skeleton;

[0010] An intermediate layer of low melting point metal is filled in the internal pores of the foam metal skeleton;

[0011] and a lower layer of low melting point metal, distributed on the lower surface of the foam metal skeleton;

[0012] The upper layer of low melting point metal is connected to the lower layer of low melting point metal through the middle layer of low melting point metal;

[0013] The melting point of the foam metal skeleton is greater than 160°C;

[0014] The melting point of the low melting point metal is 80-160° C. and is not lower than the working temperature.

[0015] In some embodiments of the present disclosure, the foam metal skeleton is foam copper.

[0016] In some embodiments of the present disclosure, the melting point of the low melting point metal is 120-160°C;

[0017] Preferably, the low melting point metal is indium.

[0018] In some embodiments of the present disclosure, the thickness of the thermally conductive gasket is 0.3-0.5 mm.

[0019] According to a second aspect of the present disclosure, a method for manufacturing a thermally conductive gasket is provided, comprising the following steps: forming a low melting point metal on the upper surface, the lower surface and the internal pores of the foam metal skeleton respectively to obtain the thermally conductive gasket.

[0020] In some embodiments of the present disclosure, the low melting point metal is formed on the upper surface, the lower surface and the internal pores of the foam metal skeleton respectively by electroplating;

[0021] The electroplating method comprises the following steps: electroplating a clean foam metal skeleton substrate placed in an electroplating solution containing a low-melting-point metal source to form a low-melting-point metal in the internal pores, upper surface and lower surface of the foam metal skeleton substrate to obtain a composite metal material; and rolling the composite metal material to obtain the thermal conductive gasket.

[0022] In some embodiments of the present disclosure, the step of heat treating the composite metal material in an inert atmosphere before rolling is also included to enhance the bonding force between the low melting point metal and the foam metal skeleton, and the inert atmosphere can prevent the formation of an oxide layer on the metal surface;

[0023] In order to effectively improve the bonding strength between the indium coating and the copper foam and avoid melting of the metal indium, preferably, the heat treatment temperature is between 135-150° C. and the heating rate is 5-10° C. / min.

[0024] In some embodiments of the present disclosure, the foam metal skeleton substrate is foam copper with a porosity of >90%, a pore density of 100-300ppi, and a thickness of 1-3mm.

[0025] In some embodiments of the present disclosure, the composite metal material is rolled to a thickness of 0.3-0.5 mm to obtain the thermally conductive gasket.

[0026] In some embodiments of the present disclosure, the electroplating solution is an indium electroplating solution;

[0027] The indium electroplating solution comprises an indium source, an acid, a surfactant, a stabilizer and a complexing agent;

[0028] Preferably, in order to achieve environmental protection and avoid pollution, the indium source is indium sulfamate, and the amount used in the electroplating solution is 60-120 g / L;

[0029] The acid is aminosulfonic acid, and the amount used in the electroplating solution is 10-50g / L;

[0030] In order to achieve a good wetting and diffusion effect speed of the indium electroplating solution to achieve a uniform electroplating effect on the surface of the foamed metal, such as foamed copper, the surfactant is didodecyl dimethyl ammonium bromide, and the amount used in the electroplating solution is 50-150 mg / L;

[0031] The stabilizer is trisodium ethylenediamine disuccinate, and the dosage in the electroplating solution is 0.8-2g / L;

[0032] The complexing agent is carboxymethyl chitosan, which can be complexed with metal ions in the electroplating solution to synergistically stabilize the electroplating solution. In order to better achieve the complexing effect, the amount of carboxymethyl chitosan in the electroplating solution is 0.2-2g / L;

[0033] The pH value of the electroplating solution is 1.5-2.5, which can be adjusted using a 1 mol / L NaOH solution.

[0034] In some embodiments of the present disclosure, the current density during electroplating is 1-2 ASD, the electroplating time is 15-25 min, and the electroplating temperature is room temperature, such as 25°C.

[0035] In some embodiments of the present disclosure, a clean foam metal skeleton substrate is obtained by pretreating the foam metal substrate;

[0036] Preferably, the pretreatment method includes ultrasonic acid washing and ultrasonic alcohol washing of the foam metal substrate; for example, immersing the foam metal substrate in a 0.5 mol / L sulfuric acid solution for ultrasonic washing, taking it out and then immersing the foam copper in anhydrous ethanol and anhydrous acetone for alcohol washing;

[0037] Furthermore, in order to achieve a better cleaning effect, the ultrasonic acid cleaning time is controlled within 4-10 minutes, and the ultrasonic alcohol cleaning time is controlled within 5-15 minutes;

[0038] Furthermore, in order to facilitate subsequent use, the foam metal substrate was placed in a vacuum drying oven at 60° C. for 1 h after ultrasonication to obtain a clean foam metal skeleton substrate.

[0039] In some embodiments of the present disclosure, the method further includes cutting the calendered thermally conductive gasket.

[0040] In some embodiments of the present disclosure, an insoluble metal should be used as the anode; further, in order to achieve the effect that the anode has high electrochemical catalytic energy, low oxygen evolution overpotential, high stability, and does not pollute the plating solution, the insoluble metal is titanium.

[0041] In some embodiments of the present disclosure, the cathode is a pre-treated clean foam metal substrate, such as a clean foam copper substrate.

[0042] Beneficial technical effects of the present invention

[0043] A thermally conductive gasket according to an embodiment of the present invention uses a foam metal with a hole structure as a skeleton, so that a low-melting-point metal can be filled in the holes of the foam metal, so that the low-melting-point metal located on the upper and lower surfaces of the foam metal can be connected through the low-melting-point metal inside the foam metal, and the thermal conductivity of the thermally conductive gasket is continuous. After the low-melting-point metal on the upper and lower surfaces generates fluidity when heated, it will be filled into the foam voids inside the foam metal under pressure to ensure that the low-melting-point metal does not leak. On this basis, the foam metal with a specific melting point is used as a skeleton material to maintain effective support for the thermally conductive gasket at the higher operating temperature (65-140°C) of high-power electronic devices; and the low-melting-point metal with a specific melting point generates micro-flow at high temperature, and can better fill the interface gaps by flowing under interface pressure, so that the thermally conductive gasket is very close between the two interfaces, thereby improving the actual thermal conductivity. Therefore, the thermally conductive gasket formed by the composite of foam metal with a specific melting point and low melting point metal of the present invention can be normally used on high-power electronic devices, solving the problem of low thermal conductivity of the thermally conductive gasket in the prior art at higher operating temperatures (65-140°C).

[0044] Preferably, the embodiment of the present invention uses copper foam as the skeleton, which can not only maintain effective support for the thermally conductive gasket at the higher operating temperature (65-140°C) of high-power electronic devices, but also the copper foam itself has a higher thermal conductivity, which is beneficial to improving the thermal conductivity of the composite thermally conductive gasket.

[0045] Preferably, the low melting point metal in the embodiment of the present invention is metallic indium. The melting point of metallic indium is about 160°C, which can ensure appropriate fluidity at higher operating temperatures (e.g., 65-140°C), prevent excessive flow, and avoid high-temperature leakage and decreased thermal conductivity. Moreover, compared with pure indium thermal pads, indium-attached thermal pads with foam metal as the skeleton can greatly reduce the amount of metallic indium used in the thermal pads, which can effectively reduce the production cost of the thermal pads.

[0046] Preferably, the preparation method of the embodiment of the present invention attaches the low melting point metal to the upper and lower surfaces of the foam metal and the inside of the foam metal by electroplating, which can achieve a good combination of the low melting point metal and the foam metal skeleton material. At the same time, the electroplating method is simple and pollution-free, which is conducive to its industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a schematic diagram of a thermally conductive gasket structure in an embodiment of the present disclosure.

[0048] Explanation of the reference numerals: 1 - foam metal skeleton; 21 - upper layer low melting point metal; 22 - lower layer low melting point metal; 23 - middle layer low melting point metal. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution of the embodiments of the present disclosure will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by those skilled in the art without creative work also fall within the scope of protection of the present disclosure.

[0050] The foam copper raw material used in Examples 2-4, Comparative Examples 1 and 4 is commercially available foam copper with a porosity of >90%, a pore density of 100 ppi, a thickness of 1 mm, and a melting point of 1083°C.

[0051] The pure copper sheet used in Comparative Example 3 has a thickness of 1 mm and a melting point of 1084.62°C.

[0052] Example 1

[0053] like Figure 1 As shown, a thermally conductive gasket provided in this embodiment includes a foam metal skeleton 1 and a low-melting-point metal; the low-melting-point metal includes: an upper layer of low-melting-point metal 21, a lower layer of low-melting-point metal 22 and a middle layer of low-melting-point metal 23.

[0054] An upper layer of low-melting-point metal 21 is distributed on the upper surface of the foam metal skeleton 1; an intermediate layer of low-melting-point metal 23 fills the internal pores of the foam metal skeleton 1; a lower layer of low-melting-point metal 22 is distributed on the lower surface of the foam metal skeleton 1; the upper layer of low-melting-point metal 21 and the lower layer of low-melting-point metal 22 are connected through the intermediate layer of low-melting-point metal 23.

[0055] The foam metal skeleton 1 is foam copper, and its melting point is 1083° C. The low melting point metal is indium, and its melting point is 156.6° C. The thermal conductive pad can be used in a temperature range of 65-150° C., such as 70-140° C., or 80-120° C.

[0056] The thickness of the thermally conductive pad is 0.3 mm.

[0057] Example 2

[0058] A method for preparing a thermally conductive pad according to embodiment 1 comprises the following steps:

[0059] The copper foam substrate was pretreated by placing the copper foam substrate in a 0.5 mol / L sulfuric acid solution for ultrasonic treatment for 5 minutes, and then placing it in acetone and anhydrous ethanol for ultrasonic treatment for 3 minutes respectively; after ultrasonic treatment, the copper foam substrate was placed in a vacuum drying oven at 60°C for 1 hour to obtain a clean copper foam substrate.

[0060] Preparation of indium electroplating solution: The indium electroplating solution contains the following ingredients: 80 g / L indium sulfamate, 20 g / L sulfamate, 60 mg / L didodecyldimethylammonium bromide, 1.2 g / L trisodium ethylenediamine disuccinate, and 0.6 g / L carboxymethyl chitosan.

[0061] Electroplating: Before electroplating, the pH value of the electroplating solution was adjusted to 2 using a 1 mol / L NaOH solution. The electroplating cathode was a pretreated clean foam copper substrate, and the anode was metallic titanium. Under a 25°C environment, 1 ASD current was applied to the electrodes for 15 min of electroplating to obtain an indium-plated foam copper composite metal material.

[0062] The indium-plated copper foam composite metal material is subjected to heat treatment: the obtained indium-plated copper foam composite metal material is placed in a nitrogen protection atmosphere, placed in a furnace for heat treatment at 150° C., and the heating rate is controlled at 5° C. / min.

[0063] Rolling and cutting: The heat-treated indium-plated copper foam composite metal material is pressed to a thickness of 0.3 mm and cut into a size of 10 cm*10 cm to obtain an indium-plated copper foam thermal conductive pad.

[0064] Example 3

[0065] A method for preparing a thermally conductive pad according to embodiment 1 comprises the following steps:

[0066] The copper foam substrate was pretreated by placing the copper foam substrate in a 0.5 mol / L sulfuric acid solution for ultrasonic treatment for 5 minutes, and then placing it in acetone and anhydrous ethanol for ultrasonic treatment for 3 minutes respectively; after ultrasonic treatment, the copper foam substrate was placed in a vacuum drying oven at 60°C for 1 hour to obtain a clean copper foam substrate.

[0067] Preparation of indium electroplating solution: The indium electroplating solution contains the following ingredients: 100 g / L indium sulfamate, 25 g / L sulfamate, 60 mg / L didodecyldimethylammonium bromide, 1.2 g / L trisodium ethylenediamine disuccinate, and 0.8 g / L carboxymethyl chitosan.

[0068] Electroplating: Before electroplating, the pH value of the electroplating solution was adjusted to 2 using a 1 mol / L NaOH solution. The electroplating cathode was a pretreated clean foam copper substrate, and the anode was metallic titanium. Under a 25°C environment, 1 ASD current was applied to the electrodes for 20 minutes of electroplating to obtain an indium-plated foam copper composite metal material.

[0069] The indium-plated copper foam composite metal material is subjected to heat treatment: the obtained indium-plated copper foam composite metal material is placed in a nitrogen protection atmosphere, placed in a furnace for heat treatment at 150° C., and the heating rate is controlled at 5° C. / min.

[0070] Rolling and cutting: The heat-treated indium-plated copper foam composite metal material is pressed to a thickness of 0.3 mm and cut into a size of 10 cm*10 cm to obtain an indium-plated copper foam thermal conductive pad.

[0071] Example 4

[0072] A method for preparing a thermally conductive pad according to embodiment 1 comprises the following steps:

[0073] The copper foam substrate was pretreated by placing the copper foam substrate in a 0.5 mol / L sulfuric acid solution for ultrasonic treatment for 5 minutes, and then placing it in acetone and anhydrous ethanol for ultrasonic treatment for 3 minutes respectively; after ultrasonic treatment, the copper foam substrate was placed in a vacuum drying oven at 60°C for 1 hour to obtain a clean copper foam substrate.

[0074] Preparation of indium electroplating solution: The indium electroplating solution contains the following ingredients: 120 g / L indium sulfamate, 40 g / L sulfamate, 60 mg / L didodecyldimethylammonium bromide, 1.2 g / L trisodium ethylenediamine disuccinate, and 1.0 g / L carboxymethyl chitosan.

[0075] Electroplating: Before electroplating, the pH value of the electroplating solution was adjusted to 2 using a 1 mol / L NaOH solution. The electroplating cathode was a pretreated clean foam copper substrate, and the anode was metallic titanium. Under a 25°C environment, a 1.5ASD current was applied to the electrode for 20 minutes of electroplating to obtain an indium-plated foam copper composite metal material.

[0076] The indium-plated copper foam composite metal material is subjected to heat treatment: the obtained indium-plated copper foam composite metal material is placed in a nitrogen protection atmosphere, placed in a furnace for heat treatment at 150° C., and the heating rate is controlled at 5° C. / min.

[0077] Rolling and cutting: The heat-treated indium-plated copper foam composite metal material is pressed to a thickness of 0.3 mm and cut into a size of 10 cm*10 cm to obtain an indium-plated copper foam thermal conductive pad.

[0078] Comparative Example 1

[0079] A commercially available foam copper with a porosity of >90%, a pore density of 100ppi, a melting point of 1083°C, and cut into 10cm*10cm, 0.3mm thick thermal conductive pads was selected.

[0080] Comparative Example 2

[0081] Commercially available foam indium was selected, with a porosity of >90%, a pore density of 100 ppi, a melting point of 156.6° C., and was cut into 10 cm*10 cm thermal conductive pads with a thickness of 0.3 mm.

[0082] Comparative Example 3

[0083] A method for preparing a thermally conductive pad comprises the following steps:

[0084] The pure copper sheet substrate was pretreated: the pure copper sheet substrate was placed in a 0.5 mol / L sulfuric acid solution for ultrasonic treatment for 5 minutes, and then placed in acetone and anhydrous ethanol for ultrasonic treatment for 3 minutes respectively; after ultrasonic treatment, the pure copper sheet substrate was dried in a vacuum drying oven at 60° C. for 1 hour to obtain a pure copper sheet substrate.

[0085] Preparation of indium electroplating solution: The indium electroplating solution contains the following ingredients: 120 g / L indium sulfamate, 40 g / L sulfamate, 60 mg / L didodecyldimethylammonium bromide, 1.2 g / L trisodium ethylenediamine disuccinate, and 1.0 g / L carboxymethyl chitosan.

[0086] Electroplating: Before electroplating, the pH value of the electroplating solution was adjusted to 2 using a 1 mol / L NaOH solution. The electroplating cathode was a pretreated pure copper sheet substrate, and the anode was metallic titanium. Under a 25°C environment, a 1.5ASD current was applied to the electrode for 20 minutes of electroplating to obtain an indium-plated copper sheet.

[0087] The indium-plated copper sheet was heat-treated: the obtained indium-plated copper sheet was placed in a nitrogen protective atmosphere, placed in a furnace for heat treatment at 150° C., and the heating rate was controlled at 5° C. / min.

[0088] Rolling and cutting: The heat-treated indium-plated copper sheet is rolled to a thickness of 0.3 mm and cut into a size of 10 cm*10 cm to obtain an indium-plated copper thermal pad.

[0089] Comparative Example 4

[0090] A method for preparing a thermally conductive pad comprises the following steps:

[0091] The copper foam substrate was pretreated by placing the copper foam substrate in a 0.5 mol / L sulfuric acid solution for ultrasonic treatment for 5 minutes, and then placing it in acetone and anhydrous ethanol for ultrasonic treatment for 3 minutes respectively; after ultrasonic treatment, the copper foam substrate was placed in a vacuum drying oven at 60°C for 1 hour to obtain a clean copper foam substrate.

[0092] Liquid metal sheet: All metals including indium, bismuth, tin and gallium are compounded in a mass ratio of 47:29.5:13.5:10 to form a liquid metal sheet that is semi-solid at room temperature, has a melting point of 45°C and a thickness of 50μm.

[0093] Rolling and cutting: The liquid metal sheet and the 1 mm thick copper foam substrate are pressed and laminated to a thickness of 0.3 mm, and then cut into a size of 10 cm*10 cm to obtain a liquid metal copper foam thermal pad.

[0094] Performance Testing

[0095] The thermally conductive pads provided in Examples 2-4 and Comparative Examples 1-4 were tested in the following manner:

[0096] Thermal conductivity: The transient plane heat source method is used to simulate the actual thermal conductivity of each thermal conductive gasket sample under the operating temperature when loaded on high-power electronic components. The actual measured temperature on the machine is 100°C.

[0097] Elastic modulus test: GB / T 22315-2008 was used to conduct high temperature tensile tests on each thermal pad sample. The test temperature was 100°C to simulate the temperature of the machine.

[0098] The test results are shown in Table 1:

[0099] Table 1. Test data

[0100] sample Thermal conductivity (W / (m·k)) Elastic modulus (E / GPa) Comparative Example 1 8.8 81.7 Comparative Example 2 6.2 12.6 Comparative Example 3 7.4 92.0 Comparative Example 4 6.7 76.2 Example 2 16.7 32.2 Example 3 15.2 28.0 Example 4 14.8 24.3

[0101] The test results in Table 1 show that under the actual measurement condition of 100°C, the thermal conductivity of the indium-plated copper foam thermal conductive pads of Examples 2-4 is significantly improved compared with the foam copper thermal conductive pads of Comparative Example 1, the foam indium thermal conductive pads of Comparative Example 2, the indium-plated copper thermal conductive pads of Comparative Example 3, and the liquid metal foam copper thermal conductive pads of Comparative Example 4. At the same time, compared with the foam copper thermal conductive pads of Comparative Example 1, the elastic modulus of the indium-plated copper foam thermal conductive pads of Examples 2-4 decreased significantly, and the elastic modulus was low, indicating that the upper and lower indium layers give the thermal conductive pads excellent flexibility when under pressure, and can well fill the contact gap between the interfaces. Moreover, the structural stability of the indium-plated copper foam thermal conductive pads of Examples 2-4 is high. Therefore, the indium-plated copper foam thermal conductive pads of Examples 2-4 have excellent actual thermal conductivity.

[0102] The foam copper thermal pad of Comparative Example 1 has a large elastic modulus and high rigidity. Under the actual measured working condition of 100°C, it is easy to have uneven deformation on the contact surface and produce interface voids. The thermal conductivity is low, so the actual thermal conductivity is low. Although the foam indium thermal pad of Comparative Example 2 has a low elastic modulus, its structural stability is poor. After it becomes fluid at the working temperature of 100°C, its foam structure will slowly collapse over time, resulting in large interface voids between the two interfaces. The actual thermal conductivity is very low, so the actual thermal conductivity is low.

[0103] The indium-plated copper thermal pad of Comparative Example 3 is a sandwich structure, with separated upper and lower indium layers, discontinuous thermal conductivity, and a low actual thermal conductivity (determined by the lowest copper layer) and a high actual elastic modulus (determined by the highest copper layer), so the actual thermal conductivity is low; in addition, the copper sheet cannot absorb the flowing indium, which easily causes indium leakage. The liquid metal foam copper thermal pad of Comparative Example 4 has low thermal conductivity, high elastic modulus, and poor structural stability, so the actual thermal conductivity is low. Since the liquid metal completely melts and leaks at an operating temperature of 100°C, it cannot fill the interface gaps, the interface gaps are large, the actual thermal conductivity is low, and it cannot increase the flexibility of the thermal pad. The thermal pad has a high elastic modulus.

[0104] Under the actual test conditions of 100°C, the thermally conductive gaskets of Examples 2-4 with upper and lower indium layers connected, with copper foam as a rigid skeleton material, can maintain the overall structural stability of the metal gasket when the indium is in a slightly molten state, and avoid the detachment of the thermal conductive interface caused by the collapse of the gasket structure; the upper and lower indium-plated layers generate microflows under the test conditions, and can better fill the interface gaps through flow under the interface pressure, increase the interface area, and make the interface contact form tend from point contact to surface contact, improve the problem of increased interface gaps caused by the difference in linear expansion coefficients of interface materials under temperature changes, and improve the actual thermal conductivity. In addition, under pressure, part of the indium of the thermally conductive gaskets of Examples 2-4 will fill the foam gaps of the copper foam, and there is no leakage of indium.

[0105] Unless the context clearly indicates otherwise, the singular form of the words used herein and in the appended claims includes the plural and vice versa. Thus, when referring to the singular, the plural form of the corresponding term is generally included. Similarly, the words "comprise" and "include" are to be interpreted as inclusive rather than exclusive. Likewise, the terms "include" and "or" should be interpreted as inclusive unless such interpretation is expressly prohibited herein. Where the term "example" is used herein, particularly when it is located after a group of terms, the "example" is merely exemplary and illustrative and should not be considered exclusive or comprehensive.

[0106] Further aspects and scopes of adaptability become apparent from the description provided herein. It should be understood that various aspects of the present disclosure can be implemented individually or in combination with one or more other aspects. It should also be understood that the description and specific embodiments herein are intended for purposes of illustration only and are not intended to limit the scope of the present disclosure.

[0107] Several embodiments of the present disclosure are described in detail above, but it is obvious that those skilled in the art can make various modifications and variations to the embodiments of the present disclosure without departing from the spirit and scope of the present disclosure. The protection scope of the present disclosure is defined by the attached claims.

Claims

1. A thermally conductive pad, characterized in that: Including foam metal skeleton and low melting point metal; The low melting point metal includes: An upper layer of low melting point metal is distributed on the upper surface of the foam metal skeleton; An intermediate layer of low melting point metal is filled in the internal pores of the foam metal skeleton; and a lower layer of low melting point metal, distributed on the lower surface of the foam metal skeleton; The upper layer of low melting point metal is connected to the lower layer of low melting point metal through the middle layer of low melting point metal; The melting point of the foam metal skeleton is greater than 160°C; The melting point of the low melting point metal is 80-160° C. and is not lower than the working temperature.

2. The thermally conductive pad according to claim 1, characterized in that: The foam metal skeleton is foam copper.

3. The thermally conductive pad according to claim 1 or 2, characterized in that: The melting point of the low melting point metal is 120-160°C; Preferably, the low melting point metal is indium.

4. The thermally conductive pad according to any one of claims 1 to 3, characterized in that: The thickness of the thermally conductive pad is 0.3-0.5 mm.

5. The method for preparing the thermally conductive pad according to any one of claims 1 to 4, characterized in that: The following steps are involved: Low melting point metal is formed on the upper surface, the lower surface and the internal pores of the foam metal skeleton respectively to obtain the thermal conductive pad.

6. The preparation method according to claim 5, characterized in that: Forming the low melting point metal on the upper surface, the lower surface and the internal pores of the foam metal skeleton respectively by electroplating; The electroplating method comprises the following steps: electroplating a clean foam metal skeleton substrate placed in an electroplating solution containing a low-melting-point metal source to form a low-melting-point metal in the internal pores, upper surface and lower surface of the foam metal skeleton substrate to obtain a composite metal material; and rolling the composite metal material to obtain the thermal conductive gasket.

7. The preparation method according to claim 6, characterized in that: The method further comprises the step of heat treating the composite metal material under an inert atmosphere before rolling; Preferably, the heat treatment temperature is between 135-150°C, and the heating rate is 5-10°C / min.

8. The preparation method according to claim 6 or 7, characterized in that: The foam metal skeleton substrate is foam copper, with a porosity of more than 90%, a pore density of 100-300ppi, and a thickness of 1-3mm.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The electroplating solution is an indium electroplating solution; The indium electroplating solution comprises an indium source, an acid, a surfactant, a stabilizer and a complexing agent; Preferably, the indium source is indium sulfamate, and the amount used in the electroplating solution is 60-120 g / L; The acid is aminosulfonic acid, and the amount used in the electroplating solution is 10-50g / L; The surfactant is didodecyl dimethyl ammonium bromide, and the dosage in the electroplating solution is 50-150 mg / L; The stabilizer is trisodium ethylenediamine disuccinate, and the dosage in the electroplating solution is 0.8-2g / L; The complexing agent is carboxymethyl chitosan, and the dosage in the electroplating solution is 0.2-2g / L; The pH value of the electroplating solution is 1.5-2.

5.

10. The preparation method according to any one of claims 6 to 9, characterized in that: The current density during electroplating is 1-2ASD, the electroplating time is 15-25min, and the electroplating temperature is room temperature.

Citation Information

Patent Citations

  • All-metal heat conducting paste and preparation method thereof

    CN105400497A

  • Heat conduction material as well as preparation method and application thereof

    CN118870740A

  • Multi-layer composite heat-conducting sheet and preparation method and application thereof

    CN119031661A